Experiments and simulations of the structure Harmony-Gamma subjected to broadband random vibrations. (October 2021) - Roncen, T.; Sinou, J.-J.; Lambelin, J.-P.
Highlights: Experiments of an industrial structure subjected to broadband random vibrations. Simulation and adaptation of the HBM for a FEM structure subjected to broadband random vibrations. A global strategy to achieve a refined understanding of the nonlinear phenomena and their origin. Abstract: The structure Harmony-Gamma is a metallic assembly representative of an industrial structure for which the vibratory response is influenced by the apparition of nonlinear phenomena within two specific types of joints, the first corresponding to friction joints and the second to elastomer joints. The present study extends the previous work based on experiments and numerical simulations of the structure Harmony-Gamma subjected to harmonic vibrations [1] . More specifically, the nonlinear vibrational behaviour of the assembly subjected to random broadband excitations is studied. Broadband excitations are performed experimentally, in order to provide a first understanding of the nonlinear effect of both the friction and elastomer joints. Additionally, a global numerical methodology based on finite-element modelling and the use of the Harmonic Balance Method for the prediction of the nonlinear response of the Harmony-Gamma structure subjected to stochastic excitation is proposed. It is demonstrated that the use of a numerical model that has been validated against experimental tests can furthermore be used to achieve a refined understanding of the nonlinear phenomena and their origin.